1987
DOI: 10.1111/j.1365-2125.1987.tb03059.x
|View full text |Cite
|
Sign up to set email alerts
|

Antipyrine metabolism in acute hepatic porphyria in relapse and remission.

Abstract: Antipyrine kinetics following a single oral dose were obtained in porphyric patients in attack and in remission and in controls. The clearance of antipyrine was significantly lower during an acute porphyric attack (median: 0.34 ml min‐1 kg‐1; range: 0.1‐0.71, P less than 0.05) than in patients in remission (median: 0.53 ml min‐1 kg‐1; range: 0.28‐0.87) or controls (median: 0.52 ml min‐1 kg‐1; range: 0.32‐ 0.93). There was a significant negative correlation between weight‐ adjusted antipyrine clearance and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Indeed, P450 activity is impaired in several heme-synthesis disorders. For example, in patients with partial genetic defects in heme synthesis enzymes, such as in acute porphyrias, the capacity to metabolize antipyrine is decreased [48].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, P450 activity is impaired in several heme-synthesis disorders. For example, in patients with partial genetic defects in heme synthesis enzymes, such as in acute porphyrias, the capacity to metabolize antipyrine is decreased [48].…”
Section: Discussionmentioning
confidence: 99%
“…Anderson et al (1976) showed that the mean plasma half-life of antipyrine was prolonged to 22 h in a group of 10 patients with porphyria in remission (eight had acute intermittent porphyria), as compared with a mean half-life of 13 h in healthy volunteers. In a group of 16 patients (14 with acute intermittent porphyria and two with variegate porphyria) the clearance of antipyrine was lower during acute attacks than during remission (Birnie et al, 1987). There was also a significant negative correlation between antipyrine clearance and the urinary excretion of porphyrin precursors.…”
Section: Introductionmentioning
confidence: 93%